2022
DOI: 10.20471/acc.2022.61.02.13
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-Hospital Cardiac Arrest Outcomes – Bystander Cardiopulmonary Resuscitation Rate Improvement

Abstract: SUMMARY Approximately 8000 people suffer from an out-of-hospital cardiac arrest (OHCA) in the Republic of Croatia every year. OHCA survival rates generally remain low despite major advances in resuscitation. Its incidence and survival rate are well known in many European countries, but reliable data on OHCA in Croatia are lacking. The aim of the study was to determine survival rate of patients with OHCA in the Republic of Croatia and the importance of the community bystander cardiopulmonary resuscit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
5
0
3
Order By: Relevance
“…8 A bystander starting CPR quickly has also been shown to increase the survival rate after an OHCA event. 9 Hands-only CPR has been shown to be as effective in the first few minutes as conventional CPR and has been shown to improve the chain of survival after a cardiac arrest, with some studies showing an increased willingness of bystanders to respond after a cardiac arrest. 10 In Nepal, Emergency Medical Services (EMS) is in its infant stages, and the health system suffers from a significant shortage of health service providers.…”
Section: Introductionmentioning
confidence: 99%
“…8 A bystander starting CPR quickly has also been shown to increase the survival rate after an OHCA event. 9 Hands-only CPR has been shown to be as effective in the first few minutes as conventional CPR and has been shown to improve the chain of survival after a cardiac arrest, with some studies showing an increased willingness of bystanders to respond after a cardiac arrest. 10 In Nepal, Emergency Medical Services (EMS) is in its infant stages, and the health system suffers from a significant shortage of health service providers.…”
Section: Introductionmentioning
confidence: 99%
“… 4 A meta-analysis of 141 studies from North America, Europe, Asia, and Oceania showed that RSC occurred in 29.7% of adult patients resuscitated in the out-of-hospital environment, and less than 10% survived until hospital discharge. 5 The highest survival rates occurred in witnessed CA cases with early initiation of resuscitation maneuvers. 5 In another meta-analysis that included 44 studies conducted in Europe, Asia, and North America, the use of extracorporeal circulation in out-of-hospital resuscitation resulted in survival rates of up to 24%, with 18% of patients having favorable neurological conditions.…”
mentioning
confidence: 98%
“… 4 Em uma metanálise que incluiu 141 estudos da América do Norte, Europa, Asia e Oceania, o RCE ocorreu em 29,7% dos pacientes adultos reanimados no ambiente extra-hospitalar e menos de 10% sobreviveram até a alta hospitalar. 5 As maiores taxas de sobrevida ocorreram na PCR presenciada e com início das manobras de reanimação de forma precoce. 5 Em outra metanálise, que incluiu 44 estudos realizados na Europa, Asia e América do Norte a utilização de circulação extracorpórea na reanimação extra-hospitalar apresentou taxas de sobrevida até a alta de 24%, e 18% dos pacientes apresentaram condições neurológicas favoráveis.…”
unclassified
See 2 more Smart Citations